Self-Compassion Psychoeducation to Enhance the Adjustment of New Students in Islamic Boarding Schools - lelikusuma; Djudiyah (Educan, 2026)
The transition to boarding school life often poses adjustment challenges for new students. Self-compassion is considered a protective factor that may facilitate adaptation during this transition. This study examined the effectiveness of self-compassion psychoeducation in enhancing self-compassion and adjustment among new students in an Islamic boarding school from the perspective of Islamic educational psychology. A quasi-experimental pretest-post-test control group design was employed involving 82 first-year female students consisting of an intervention group (n = 41) and a control group (n = 41). Data were collected using the Self-Compassion Scale (SCS) and the Student Adjustment Scale (SAS). Gain scores (post-test-pretest) were analysed using independent-samples t-tests. The results showed that the intervention group demonstrated significantly greater improvements in self-compassion (t (80) = 7.651, p < .001, d = 1.69) and adjustment (t (80) = 5.069, p < .001, d = 1.12) than the control group. These findings indicate that self-compassion psychoeducation is effective in strengthening self-compassion and improving adjustment among new students in Islamic boarding schools.